A Study on the Attachment to Pets Among Owners of Cats and Dogs Using the Lexington Attachment to Pets Scale (LAPS) in the Basque Country - Eider Egaña-Marcos; Olatz Goñi-Balentziaga; Garikoiz Azkona (Animals)
The relationship between humans and their pets has long fascinated researchers, particularly in exploring how attachment varies according to the type of pet. Cats and dogs exhibit unique behavioral and social traits that influence the dynamics of human–pet relationships. Moreover, specific human characteristics have been found to affect this attachment. Our study examines the human factors that influence pet attachment among cat and dog owners in the Basque Country, located in northern Spain. By investigating these elements, our research aims to enhance the understanding of how human factors shape the human–animal bond. The study included a total of 202 participants, of whom 66.8% were dog owners, and 74.8% identified as women, with ages ranging from 18 to 74 years. Consistent with many previous studies, our results indicate that attachment is generally stronger with dogs compared to cats and that owner’s characteristics such as being female, younger, not living with children, and the amount of time spent with pets on weekends are linked to stronger attachments to pets.